PENGARUH LITERASI DIGITAL, KEMAMPUAN BERPIKIR KRITIS, DAN KEMAMPUAN BERPIKIR KREATIF TERHADAP KINERJA MENGAJAR PADA GURU SD NEGERI DI KECAMATAN JOMBANG KOTA CILEGON - Diana Hervina; Muhammad Suparmoko; Ahmad Mukhlis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The rapid advancement of the digital era has transformed educational practices and requires elementary school teachers to possess adequate digital literacy skills. Digital literacy is essential in supporting effective and innovative learning and in enhancing higher-order thinking skills, particularly critical and creative thinking, which contribute to teaching performance. This study aims to examine the effect of digital literacy on teachers’ critical and creative thinking abilities and its implications for teaching performance among elementary school teachers. This study employed a quantitative approach using a survey method. The participants were 185 elementary school teachers in Jombang District, Cilegon City, Indonesia. Data were collected through structured questionnaires and analyzed using Structural Equation Modelling (SEM) with a Partial Least Square (PLS) approach using SmartPLS 4. The analysis involved testing the validity, reliability, and structural relationships among the research variables. The results indicate that digital literacy has a positive and significant effect on teachers’ critical and creative thinking abilities. Moreover, digital literacy directly and significantly influences teaching performance. Both critical thinking and creative thinking abilities also show significant positive effects on teaching performance. These findings suggest that digital literacy plays a crucial role in enhancing higher-order thinking skills, which in turn improves teachers’ instructional performance. In conclusion, strengthening teachers digital literacy is essential for improving teaching quality in elementary education. Continuous professional development programs focusing on digital competence and higher-order thinking skills are therefore strongly recommended.